Laparoscopic surgery in rectal cancer patients taking anti-thrombotic therapy. Issue 4 (31st July 2020) - Nozawa, Hiroaki; Shinagawa, Takahide; Kawai, Kazushige; Hata, Keisuke; Tanaka, Toshiaki; Nishikawa, Takeshi; Sasaki, Kazuhito; Kaneko, Manabu; Murono, Koji; Emoto, Shigenobu; Sonoda, Hirofumi; Ishihara, Soichiro
Abstract: Background: Several previous studies have shown that laparoscopic resection of rectal cancer is a feasible option. However, its safety and efficacy in patients receiving long-term anti-thrombotic therapy (AT) remain unclear. Material and methods: We retrospectively reviewed 364 patients who underwent elective resection for rectal cancer via a laparoscopic approach between 2007 and 2018 in our institute. Patients were classified according to the long-term use of AT. AT was interrupted perioperatively with or without heparin bridging therapy in all anti-thrombotic users. Clinicopathological factors and surgical outcomes were analyzed between patient groups. Results: Thirty-two patients (9%) receiving AT were older and had lower albumin and hemoglobin levels than those not receiving AT (the non-AT group), and were predominantly male. Estimated blood loss and operative time in the AT group (median: 50 mL and 294 min) did not differ from those in the non-AT group (median: 20 mL and 295 min). There were no intergroup differences in the frequencies of other postoperative complications and oncological outcomes. Conclusions: Our results at the very least can support that laparoscopic surgery for rectal cancer is a safe and feasible option for patients taking long-term AT discontinued perioperatively.